Penerapan Metode Design Thinking Dalam Perancangan Aplikasi Pemesanan Galon - Muhammad Fajar Ahadi; Arif Amrulloh (Jurnal Ilmu Komputer dan Desain Komunikasi Visual, 2023)
The high public interest in drinking water has encouraged the growth of depots everywhere, especially in the Bobosan area located in the North Purwokerto district. However, the refill water depot and the community have some problems or obstacles in the implementation of its services such as the courier from the depot often having difficulty finding the address when delivering refill water orders when the deliverer is not a subscription Courier, difficulty in ordering gallons, limited ordering media using WhatsApp media while users can only get WhatsApp contact, and the recording of sales data and customer data is still done manually so that the monitoring process is often missed gallons resulting in several gallons lost or reduced from stock. Based on these problems, the researchers realized that a more efficient and organized solution was needed to manage the gallon ordering process. Therefore, the idea was obtained to create an application design that focuses more on the user experience and creates innovations that are relevant to user needs. The design of this application is built by applying the Design Thinking method and tested using the system Usability Scale. This study has the purpose of measuring the effective and efficient level of the gallon ordering process. The results of this study consisted of problem statements, how might we, user persona, user journey map, information architecture, wireframe, flowchart, design system, and high fidelity. Then proceed with the testing of W-Fill Application Design and obtain an average score of 80.83, where the score of 80.83 is included in the category of Excellent with grade scale A. The score indicates that the design of the W-Fill application is acceptable effective and efficient enough to assist users in ordering gallons.